IDENTIFIKASI GEJALA STRES AKADEMIK PADA SISWA DILIHAT DARI GEJALA EMOSIONAL DI SMA N 17 TEBO - Apriyanto, Yudi; Rasimin, Rasimin; Yusra, Affan (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This research is aims to look at the emotional symptoms of academic stress in students at SMA Negeri 17 Tebo using descriptive quantitative methods with persentase analysis Formula C. This research took 80 respondents from students at SMA Negeri 17 Tebo. The results of this research show that the emotional symptoms of academic stress in SMA Negeri 17 Tebo as a whole are at a percentage level of 54.06% and are in the medium category.It can be concluded that the academic stress experienced by students at SMA Negeri 17 Tebo requires special intervention from teachers and the school so that it does not become a high level.